Simulated tele-management for teaching medical students on primary health care managerial decision making - Peralta-Quispe, Felipe (2022)
Introduction: Medical students are poorly prepared in health services management due to the use of traditional teaching methods, developed in theoretical environments with poor active participation. Virtual simulated training is an innovative alternative in the learning process. Objective: This study aimed to determine the knowledge improvement in managerial decision-making amongst medical students at the Universidad Nacional Mayor de San Marcos in Peru, after a virtual simulated training. Methods: A before-after cross-sectional design was undertaken among final year medical students to measure their improvement in management knowledge. The simulation methodology was used as a component of the Medical Externship clinical course in which the administrative dimension of a clinical case such as hypoacusis was considered. Results: Of the 79 participants, 48 (60.8%) were female and the median age was 25 years. There was a median satisfaction level of 3.8 and the performance median score was 17. The median post-test rank scores were higher and statistically significant than pre-test rank scores (p = 0.004); post-test scores for males (p-value = 0.05) and females (p = 0.03) were also statistically higher than pre-test scores. Conclusion: The non-clinical simulation experience improves the knowledge on managerial decision making. It also opens opportunities to work on management issues in clinical courses, providing a comprehensive learning experience. On the other hand, it is an innovative experience where a clinical course adopts a management component.